PRAKTIK INTERNASIONALISASI MEDIA BERITASATU MEDIA HOLDINGS - Anis Endang SM (UNIVED PRESS, Universitas Dehasen Bengkulu, 2015)
This study aimed to determine the practice of internationalization carried out by BeritaSatu Media Holdings in supporting global economic interests of Lippo Group Company. Internationalization is an implication of media industrialization which the media company owner sought to reduce the spatial distance to obtain greater profits. Theory of Political Economy Media used to see how media content represents the interests of certain political economy, especially from media owners. To view the practice of internationalization, the concept of spatialization was used. The analysis showed that the practice of internationalization was done by BeritaSatu Media Holdings visible from nine of thirteen brand-owned media were in English, the media focused on business economics and finance or the life of the upper class, BeritaSatu Media Holdings’ media distribution limited in cosmopolitan areas, some media published in Indonesia (The Straits Times, ThePeak) had editions in other countries, such as Malaysia, Singapore, and Hong Kong. Of this trend was seen that the reader of BeritaSatu Media Holdings was segmented to the expatriate community and executives. The expatriate community and executives were capital market investors and financial markets, or the part of policy makers in the field of economy both in the private and public sectors who have the power or role for the current financial turnaround either within the scope of national, regional, and multinational.